Classification of and individual treatment strategies for complex tethered cord syndrome - Lin, Hepu; Su, Hui; Li, Cuicui; Zhang, Pengfei; Xiu, Bo; Bai, Yunjing; Xu, Ruxiang (Frontiers in Surgery, 2024)
Objective: To study the classification, diagnosis, and treatment strategies of complex tethered cord syndrome (C-TCS) on the basis of the patients' clinical symptoms, imaging findings, and therapeutic schedule.Methods: The clinical data of 126 patients with C-TCS admitted to our department from January 2015 to December 2020 were retrospectively analyzed. Classification criteria for C-TCS were established by analyzing the causes of C-TCS. Different surgical strategies were adopted for different types of C-TCS. The Kirollos grading, visual analogue scale (VAS), critical muscle strength, and Japanese Orthopaedic Association (JOA) scores were used to evaluate the surgical outcomes and explore individualized diagnosis and treatment strategies for C-TCS.Results: C-TCS was usually attributable to three or more types of tether-causing factors. The disease mechanisms could be categorized as pathological thickening and lipomatosis of the filum terminal (filum terminal type), arachnoid adhesion (arachnoid type), spina bifida with lipomyelomeningocele/meningocele (cele type), spinal lipoma (lipoma type), spinal deformity (bone type), and diastomyelia malformation (diastomyelia type). Patients with different subtypes showed complex and varied symptoms and required individualized treatment strategies.Conclusion: Since C-TCS is attributable to different tether-related factors, C-TCS classification can guide individualized surgical treatment strategies to ensure complete release of the tethered cord and reduce surgical complications.